Determinants of Unemployment Rate in Central Java Province in the Last Decade - Fitrianitha, Dessy (Universitas Batanghari, 2024)
This research aims to analyze the influence of wages, population growth, economic growth, and inflation on the unemployment rate in Central Java Province over the last decade. This study is a desk study that utilizes secondary data spanning 10 years, from 2013 to 2022. The required data includes wages, population growth, economic growth, inflation, as well as the unemployment rates of both women and men in Central Java Province. The independent variables in this study are wages, population growth, economic growth, and inflation, while the dependent variable is the unemployment rate in Central Java Province. The research object includes 35 regencies/cities in Central Java. Multiple Linear Regression is used for data analysis. The research findings indicate that wages, population growth, and economic growth significantly impact the unemployment rate, while inflation does not have a significant effect on the unemployment rate in Central Java Province over the last decade.